Exchange Rate Pass Through To Import Prices In Indonesia: Evidence Post Free Floating Exchange Rate - Isnowati, Sri; Setiawan, Mulyo Budi (International Journal of Economics and Financial Issues, 2017)
The aim of this research was to examine the interdependence between import price, exchange rate, national income and inflation. The data analysis method used was structural vector autoregresive (SVAR). The analysis was conducted on the impulse response function (IFRS) and forecast error variance decompositions (FEDVs) to determine the effect of exchange rate to import price and national income. The results show that the degree of exchange rate pass through was incomplete. The exchange rate shock had positive effect on import price and had negative effect on national income. Meanwhile, the effect of inflation on import price was negative. Furthermore, FEDVs analysis show that the variations of import price were largely determined by the import price, and the exchange rate variations were largely determined by the exchange rate itself. The research results show that exchange rate, national income and inflation were gradually getting stronger and gave permanent effects. Keywords: import price, exchange rate, SVAR. JEL Classifications: E6, F4